Les structures et le mobilier du site d’habitat Hallstatt final-La Tène ancienne d'Allaines Mervilliers (Eure-et-Loir) - Diane Casadei; Richard Cottiaux; Hervé Sellès (Revue Archéologique du Centre de la France)
The discovery of settlement structureson posts and of a pit Hallstatt D-early La Tène during a rescue archaeology operation in 1998, in Allaines Mervilliers (Eure-et-Loir). It concerned two rectangular buildings of six post holes, a rectangular building in three naves and a circular building. The latter two are new for this period in the Centre region.The rectangular building in three naves consisted of two central rows of three post holes and two lateral rows of four post holes. The central holes of post introduce a stratified fill, the upper layer of which produced the majority of the abundant finds. From the ceramic remains it was estimated that there were fifty-six individuals in different vases. The circular building consisted of a ring of nine post holes also producing a stratified fill. Fewer articles were discovered in this structure than in the previous building, but it too was notable for the presence of human ossuaries.